"The Soul Should Have Been Brought along": The Settlement of Skolt Sami to Inari in 1945–1949 - Lehtola, Veli-Pekka (Journal of Northern Studies, 2018)
In the autumn of 1944, five hundred Skolt Sami were forced to leave their home region in the Pechenga (Petsamo) area together with other inhabitants. After the war, their fate was discussed by Finnish officials and in the media. The question was whether they should be returned to the Soviet Union or relocated to Finland. This article describes the five-year-long process to relocate the Skolt Sami to the Inari region. Following a recommendation by Håkan Rydving to focus studies on Sami agency, in addition to non-Sami actors whose role is usually emphasised, the aim of this article is to identify key actors who made crucial choices in the relocation process. In addition to the Finnish “Skolt friend” Karl Nickul, the Skolt Sami meetings and Jaakko Sverloff, the trustee of the Skolts, appear to have had important roles in key decisions, for example regarding the expansion of the Skolt area from Nellim to Sevettijärvi, the role of the winter village and the choice of settlements along the waterways.